2014
DOI: 10.1002/ange.201409676
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Activation Upon Reduction of a Triiron(II) Complex

Abstract: Reaction of a trinuclear iron(II) complex, Fe3Br3L (1), with KC8 under N2 leads to dinitrogen activation products (2) from which Fe3(NH)3L (2‐1; L is a cyclophane bridged by three β‐diketiminate arms) was characterized by X‐ray crystallography. 1H NMR spectra of the protonolysis product of 2 synthesized under 14N2 and 15N2 confirm atmospheric N2 reduction, and ammonia is detected by the indophenol assay (yield ∼30 %). IR and Mössbauer spectroscopy, and elemental analysis on 2 and 2‐1 as well as the tri(amido)t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The bis(nitrido)‐bridged triiron‐dipotassium complex also serves as an isolable intermediate which can bind and liberate dinitrogen reversibly (Scheme ) 60. Similar cleavage of dinitrogen to form imido/amido‐bridged species using a triiron system has been reported where a stoichiometric amount of ammonia is obtained on further treatment with hydrogen chloride 65…”
Section: Stoichiometric Activation Of Dinitrogensupporting
confidence: 67%
“…The bis(nitrido)‐bridged triiron‐dipotassium complex also serves as an isolable intermediate which can bind and liberate dinitrogen reversibly (Scheme ) 60. Similar cleavage of dinitrogen to form imido/amido‐bridged species using a triiron system has been reported where a stoichiometric amount of ammonia is obtained on further treatment with hydrogen chloride 65…”
Section: Stoichiometric Activation Of Dinitrogensupporting
confidence: 67%
“…However,t here are only limited examples of the catalytic conversion of N 2 into NH 3 . [1,2] In 2003, Schrock and Yandulov reported the first example of the catalytic formation of NH 3 from N 2 under ambient reactionc onditions using aM o À N 2 complex bearing at riamidoamine ligand. [3] In 2010, our group reported that N 2 -bridged Mo 2 ÀN 2 complexes bearing PNP-typep incerl igands worked as the most effective catalysts for the catalytic formation of NH 3 from N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[H­(DMF)]­[OTf] (DMF = dimethylformamide) was prepared as described previously . Deuterated 9,10-dihydroanthrancene ( d 4 -DHA), the ligand H 3 L, and tricopper complex 1 , were synthesized as reported previously. ,, …”
Section: Methodsmentioning
confidence: 99%